ANALISIS PEMBERIAN BEA MASUK DITANGGUNG PEMERINTAH (BM DTP) TAHUN 20101 - Samosir, Agunan (Badan kebijakan Fiskal, 2012)
To augment people's purchasing power, to maintain business resilience and to raise business and industry's competitiveness, Government with its fiscal policy provides BMDTP facility. The provision was initiated with the intention to lessen the crisis impact in the midst of 2008. The measure was expected to be able to provide sufficient public goods and services. Besides, the effected real sektor may survive and raise its competitiveness. The quick research by PKAPBN concluded that the realized facility utilization trough BMDTP by Government was not optimal. The causes of low realization of BMDTP were identified, among others : (1J the mismatch between BMDTP provision with the needed sektors or industries; [2] the delayed issuance of PMK and BMDTP technical guidance; (3) the lack of knowledge of Ministry/Institution Financial Disbursement Official (Pembina K/L and KPA) on the industries having the access to acquire BMDTP. Government needs to review the cost and benefit of BMDTP on industries. The cost may be reviewed from production, and contribution on tax payment and employment creation. The Ministry/Institution or Echelon 1 which can evaluate BMDTP is FPO, MOF as the coordinator or chair of the evaluation team, and well supported by each Ministry/Institution responsible for particular industry. The task has been conducted by FPO since August 2010 and is still ongoing. In accordance with article 9 in each PMK BMDTP 2010, the evaluation timeliness may be extended to the end of February 2011.